Constitutional Principles Of Judiciary: Peculiarities Of Formalization In The Cis Countries - Treskov, Aleksej P.; But’ko, Lyudmila V.; Dzidzoev, Ruslan M.; Novikova, Alevtina E.; Solovyev, Andrey A. (Cuestiones Políticas, 2020)
The modern principles of judiciary, being an integrative constitutional-theoretical category, are the object of scientific research from the point of view of a meaningful interpretation, as well as the specific nature of formalization, including its the comparative legal aspect. In this regard, the research subject of this article is represented by the norms of the constitutions of the member states of the Commonwealth of Independent States. The article presents the analysis results, which allowed us identifying the non-standard approaches to consolidate the constitutional principles of the judiciary in the focus group of acts. We associate these approaches with the compositional specific nature of principle reflection, as well as with the variably-substantive aspect, which quantitatively and qualitatively supplements the standard list of required fundamental ideas.